2021
DOI: 10.1101/2021.10.16.464454
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

Amyloid-beta and tau pathologies are both necessary to induce novel stage-specific microglia subtypes during Alzheimer’s disease progression

Abstract: It is unknown whether specific microglia are selectively induced by amyloid-β(Aβ), tau pathologies, or both in combination. To address this, we use single-cell RNA-sequencing to profile mice bearing both Aβ and tau pathologies during Alzheimer's disease (AD). We identify novel microglia subtypes induced in a disease stage-specific manner. We show that during early-stage disease, interferon signaling induces a subtype of microglia termed EADAM. During late-stage disease, a second microglia subtype termed LADAM … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 85 publications
(99 reference statements)
0
1
0
Order By: Relevance
“…Mice do not express Siglec-8, but Siglec-F is a likely functional orthologue of Siglec-8. Siglec-F was upregulated on a subset of reactive microglia in models of neurodegeneration, and it was observed that Siglec-F is dependent on Aβ deposition at early AD stages [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%
“…Mice do not express Siglec-8, but Siglec-F is a likely functional orthologue of Siglec-8. Siglec-F was upregulated on a subset of reactive microglia in models of neurodegeneration, and it was observed that Siglec-F is dependent on Aβ deposition at early AD stages [ 32 , 33 ].…”
Section: Resultsmentioning
confidence: 99%